2017
DOI: 10.1055/s-0037-1598247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Factors in Neonatologists' Counseling for Periviable Pregnancies

Abstract: Neonatologists have varying counseling practices for women with threatened periviable pregnancies. Previous research has suggested this variability may be influenced by social and economic factors of the mother. The objective of this study was to determine the relative influence of maternal factors in counseling recommendations for periviable pregnancies. A national cohort of neonatologists was sent a web-based survey. Five maternal characteristics were varied across eight vignettes: age, education, race, pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Some participants were even uncomfortable talking about it. Other studies on the impact pf parents’ characteristics on decision-making for resuscitation of EPIs focused mainly on the impact of race, marital status, or financial resources and as such were not directly comparable with our results ( 38 40 ). However, another Belgian study on nurses’ and neonatologists’ perceptions on end-of-life decisions found that some struggle to consider parents’ socioeconomic status and that others reflect on its ethical implications ( 41 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Some participants were even uncomfortable talking about it. Other studies on the impact pf parents’ characteristics on decision-making for resuscitation of EPIs focused mainly on the impact of race, marital status, or financial resources and as such were not directly comparable with our results ( 38 40 ). However, another Belgian study on nurses’ and neonatologists’ perceptions on end-of-life decisions found that some struggle to consider parents’ socioeconomic status and that others reflect on its ethical implications ( 41 ).…”
Section: Discussioncontrasting
confidence: 99%
“…28 Finally, in 3 studies, researchers found that maternal characteristics can also influence physicians' attitudes toward resuscitation. In Kunkel et al, 39 parity, planned pregnancy, and race had a statistically significant impact on physicians' willingness to resuscitate an EPI. Similarly, in 2 studies in which physicians were asked to give opinions on 2 scenarios in which EPIs' characteristics remained constant but maternal characteristics (eg, age, marital status, parity) varied, maternal characteristics were found to significantly affect physicians' willingness to resuscitate.…”
Section: Impact Of Physicians' Characteristics On Attitudes Toward Parental Requestsmentioning
confidence: 94%
“…We found 2 exceptions to these trends. 27,32 variability of physicians' attitudes influenced by non-patient-related factors found that maternal characteristics 39,44,47 and fear of litigation 28 greatly affected physicians' attitudes. We also found that certain physicians' demographic characteristics also have an impact, suggesting that an interplay of various factors, rather than GA alone, influences physicians' attitudes.…”
Section: Physicians' Attitudes Toward Resuscitation and Nonresuscitationmentioning
confidence: 99%
“…Similarly, physicians may not be fully equipped to clarify parental values and fail to recognise that parental perspectives can be unclear and open to interpretation or misinterpretation. 15,[36][37][38] This can make it challenging to provide guidance and support to parents. One perspective can be interpreted differently by different parents and lead to different decisions, so that some will decide to initiate intensive care treatment and others comfort care, based on the same perspective.…”
Section: Discussionmentioning
confidence: 99%